(3edGHS GdCfhGQ heXGgQ GdCSQGQs - (3eMeO Hf bGSe Hf OGhO GdSdhjs
(3ChdgG (B:s
(3jHOC HeG ai ShQI GdCYQGa ef CSeGA Gddg JYGdi hUaGJg Hbhdg (B: (3Gddge jG CcQe ehdi ecf YHjOg ai GdGQV hLYd dge ajgG eYGjT s
(3BNQgG (B:s
(3jfJgi HeG ai ShQI Gdcga ef CSeGA Gddg JYGdi hUaGJg Hbhdg hef GdeDefjf Hc SHMGfc hHedGFcJc hcJHc hQSdc CjeG EjeGf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs